MODEL KEMITRAAN INTI-PLASMA PADA PERKEBUNAN KELAPA SAWIT RAKYAT YANG DIKELOLA SEPENUHNYA OLEH PERUSAHAAN INTI (Studi pada KUD Krida Sejahtera di Provinsi Lampung): Suharno, Yuprin A.D., Trisna Anggreini (Agrienvi: Jurnal Ilmu Pertanian, 2020)
The Core-Plasma partnership model is one of the patterns of community plantation development thathas been developed by the government since the 1990s by utilizing the Credit scheme for PrimaryCooperatives for Members (KKPA). This research was conducted at the Krida Sejahtera Village UnitCooperative in Lampung Province as a representation of plasma farmers in the implementation of a coreplasma partnership with PT. Sumber Indah Perkasa (SIP) as a core company. The objectives of this study are:(1) Knowing the description of the Krida Sejahtera Village Unit Cooperative in relation to the implementation ofthe nucleus-plasma partnership model of smallholder oil palm plantations in its working area, (2) Analyzing thefinancial condition of plasma plantation management by the nucleus company as a manager, (3 ) Analyzingthe socio-economic impacts of developing smallholder oil palm plantations through this partnership model.Research methods through data collection in the field through Focus Group Discussion (FGD), in-depthinterviews, and secondary data collection. The results showed: (1) Krida Sejahtera Village Unit Cooperative,which was established since 1994, has developed well, as seen from the value of assets owned in 2015amounting to Rp 117,149,211,636.00 with the number of Village Unit Cooperatives members totaling 17,255people spread over 8 districts; (2) With the application of good agricultural practices and good managementpractices the productivity of plasma plantations with plant ages ranging from 16-21 years to reach 24.85 tonsof FFB / ha / year, exceeds the theoretical potential of 22 tons. The average farmer's income reaches Rp.19,792,455 / ha / year; (3) The development of community oil palm plantations through the nucleus-plasmapartnership pattern at the research location has been shown to have a positive impact on the householdwelfare of plasma farmers.Keywords: Partnership Model, Village Unit Cooperative